Said Nursi and science in Islam character building through Nursi's Mana-i harfi - Aydın, Necati (Economist) (Routledge studies in religion, 2019)
This book examines how the prominent Muslim scholar Said Nursi developed an integrative approach to faith and science known as the other indicative (mana-i harfi) and explores how his aim to reconcile two academic disciplines, often at odds with one another, could be useful in an educational context. The book opens by examining Nursi's evolving thought with regards to secular ideology and modern science. It then utilizes the mana-i harfi approach to address a number of issues, including truth and certainty, the relationship between knowledge and worldview formation, and the meaning of beings and life. Finally, it offers a seven-dimensional knowledge approach to derive meaning and build good character through understanding scientific knowledge in the mana-i harfi perspective. This book offers a unique perspective on one of recent Islam's most influential figures, and also offers suggestions for teaching religion and science in a more nuanced way. It is, therefore, a great resource for scholars of Islam, religion and science, Middle East studies, and educational studies.